Gamma- and Cosmic-Ray observations with the GAMMA-400 Gamma-Ray telescope. Issue 9 (1st November 2022) - Topchiev, N.P.; Galper, A.M.; Arkhangelskaja, I.V.; Arkhangelskiy, A.I.; Bakaldin, A.V.; Cherniy, R.A.; Chernysheva, I.V.; Gudkova, E.N.; Gusakov, Yu.V.; Dalkarov, O.D.; Egorov, A.E.; Kheymits, M.D.; et al.
Abstract: The future space-based GAMMA-400 gamma-ray telescope will operate onboard the Russian astrophysical observatory in a highly elliptic orbit during 7 years to observe Galactic plane, Galactic Center, Fermi Bubbles, Crab, Vela, Cygnus X, Geminga, Sun, and other regions and measure gamma- and cosmic-ray fluxes. Observations will be performed in the point-source mode continuously for a long time (∼100 days). GAMMA-400 will measure gamma rays in the energy range from ∼ 20 MeV to several TeV and cosmic-ray electrons + positrons up to several tens TeV. GAMMA-400 instrument will have very good angle and energy resolutions, high separation efficiency of gamma rays from cosmic-ray background, as well as electrons + positrons from protons. The main feature of GAMMA-400 is the unprecedented angular resolution for energies > 30 GeV better than the space-based and ground-based gamma-ray telescopes by a factor of 5–10. GAMMA-400 observations will permit to resolve gamma rays from annihilation or decay of dark matter particles, identify many discrete sources, clarify the structure of extended sources, specify the data on cosmic-ray electron + positron spectra.